Perceived Instructor’s Emotional Support and its Mediating Effect to Students’ Academic Resilience and Study Engagement: In the Case of a Higher Education Institution in the Philippines - Joseph Lobo (Interpersona: An International Journal on Personal Relationships)
This investigation delved deep into the invisible threads binding student resilience and educational support. Against the backdrop of bustling classrooms and echoing halls, this research sought to unravel how these intertwined factors sculpt students’ academic journeys and well-being. In this regard, the study aimed to examine the mediating role of perceived instructor’s emotional support among 896 students [371 males (41.31%) and 527 females (58.69%)] from a selected higher education institution in the Philippines. Sex differences were notable, with female students generally reporting higher academic resilience and greater perceived emotional support from instructors compared to males. However, both sexes showed similar levels of study engagement. Correlation analyses indicated positive associations: academic resilience correlated positively with study engagement and perceived emotional support, while emotional support correlated positively with study engagement. Path analyses affirmed all hypotheses: academic resilience positively influenced study engagement and perceived emotional support. Perceived emotional support also positively influenced study engagement, partially mediating the relationship between resilience and engagement. These findings underscored the pivotal roles of resilience and emotional support in nurturing student engagement and well-being within higher education contexts. The study suggests practical implications, including the importance of enhancing instructor training in emotional support strategies and implementing resilience-building interventions to foster student success and well-being.